Crowing sound and inbreeding coefficient analysis of Pelung chicken (Gallus gallus domesticus) - BUDI S. DARYONO; MIFTAHUL MUSHLIH; AYUDHA BAHANA ILHAM PERDAMAIAN (Society for Indonesian Biodiversity, 2021)
Daryono BS, Mushlih M, Perdamaian ABI. 2021. Crowing sound and inbreeding coefficient analysis of Pelung chicken (Gallus gallus domesticus). Biodiversitas 22: 2451-2457. Pelung is one of the crowing-typed chickens from Indonesia. The bioacoustics characters of Indonesian crowing-typed chicken especially Pelung chicken were less documented. This study aimed to characterize crowing sound and to study the inbreeding coefficient of the Pelung chicken. In this study, crowing voice of 77 male Pelung chicken was recorded. Bioacoustics analyses of crowing voice were done using Adobe Audition CS5.5 and PRAAT 5.3.66 software. The results showed that chicken crowing consisted of front sound (first syllable), middle sound (second syllable) and end sound (third syllable). Each section of Pelung crowing had specific characteristics compared to other chicken breeds and varied among champions and nonchampions. Champion chicken had slowed and clear first and second syllable, sound energy was lower in first syllable then decrease at second syllable and has bitu gantung third syllable. Crowing duration and fundamental frequency (F0) of champion and non-champion were not statically different. The inbreeding coefficient reached 0.53 in several Pelung champions. Based on the research findings, bioacoustics software was applicable to assist the chicken show.